Maternal-fetal attachment and interrelated factors in pregnant women assisted in Primary Health Care - Cássio de Almeida Lima; Maria Fernanda Santos Figueiredo Brito; Lucineia de Pinho; Sélen Jaqueline Souza Ruas; Romerson Brito Messias; Marise Fagundes Silveira (Universidade de São Paulo, 2024)
Objective: to analyze maternal-fetal attachment and interrelated factors in pregnant women assisted in Primary Health Care. Method: a cross-sectional, population-based, analytical epidemiological survey. A sample of 937 participants attended by Family Health Strategy teams was investigated. Maternal-fetal attachment (outcome), sociodemographic and clinical variables, social support, family functionality, depressive symptoms and perceived stress were assessed. Multivariate analysis was adopted using structural equation modeling. Results: maternal-fetal attachment had an average of 92.6 (SD=±15.3). The adjusted structural model showed that the following factors had a direct effect on the outcome: gestational weeks (β=0.29; p<0.001), household crowding (β=-0.07; p=0.027), depressive symptoms (β=-0.11; p=0.003), social support (β=0.08; p<0.001) and family functionality (β=0.19; p<0.001). Indirect effects of social support (β=-0.29; p<0.001) and family functionality (β=-0.20; p<0.001) were identified, mediated by depressive symptoms. Conclusion: a set of interrelationships was identified between maternal-fetal attachment, gestational weeks, household crowding, depressive symptoms, social support and family functionality. It is suggested that the Family Health Strategy offer prenatal care anchored in integrality and humanization, which promotes biopsychosocial well-being during pregnancy and healthy maternal-fetal attachment.